A systematic review of the long-term benefits of school mental health and wellbeing interventions for students in Australia - Berger, Emily; Reupert, Andrea; Allen, Kelly-Ann; Campbell, Timothy Colin Heath (Frontiers in Education, 2022)
Background: Over the last decade there has been increased recognition about the role of school staff in preventing mental ill health and promoting wellbeing in young people. Despite this, information regarding the long-term benefits of school mental health programs is not widely available. Aims: The aim of this systematic review was to synthesise the evidence for school-based mental health programs which are available in Australia and have been shown to have long-term benefits for children and adolescents. Results: This systematic review of the literature identified 74 articles reporting long-term outcomes for student mental health and wellbeing, distributed across 29 unique programs. Common features of efficacious programs included cognitive behavioural interventions, mental health literacy, and social-emotional skills programs. Conclusions: Some of the identified school-based interventions for student mental health and wellbeing demonstrated long-term positive impacts on students’ physical and psychological health and wellbeing.